Orobanche Laxissima Uhlich & Rätzel (Orobanchaceae) – A New Species for Dagestan (Russia) and Azerbaijan - Piwowarczyk, Renata; Tatanov, Ivan (Biodiversity: Research and Conservation, 2015)
Orobanche laxissima Uhlich & Rätzel (Orobanchaceae) is a probably endemic Caucasian parasite of trees. New localities of this species are reported from the Greater Caucasus: Russia (Dagestan) and Azerbaijan. These are the easternmost sites known for the species, so they extend its distribution range. Its hosts, abundance, and habitat preferences at the new localities are described, and a supplemented map of distribution of this species in Caucasus Mts. is provided